SMART INNOVATIVE APPROACH FOR DESIGNING FLUVOXAMINE LOADED BIO-NANOSUSPENSION FOR THE MANAGEMENT OF DEPRESSION - Tyagi, Yogita; Madhav, N. V. Satheesh (International Journal of Applied Pharmaceutics, 2019)
Objective: Design and evaluation of fluvoxamine loaded bio-nanosuspensions using biopolymer which was isolated from the wood of Santalum album used as the stabilizer. Methods: The main aim of the present investigation was to obtain an ocular drug delivery system with improved stability using biopolymer. The fluvoxamine loaded Bio-nanosuspension was prepared using novel biopolymer isolated from Santalum album by sonication solvent evaporation method with different ratios (1%, 2%, 3%, 4% and 5%) and evaluated for particle size, polydispersity index, zeta potential, pH stability studies, %entrapment efficacy, in vitro drug release, stability studies. Results: The prepared bio-nanosuspension was subjected to the best formulation based on the comparison of above-mentioned evaluation parameters, so Fb3 (3%) formulation was found to be the best formulation showing an R2 value of 0.9744, T50% of 31.3 h and T80% of 50.1 h respectively. According to the release kinetics, the best fit model was found to be Peppas Korsmeyer with Fickian Diffusion (Higuchi Matrix) as the mechanism of drug release. Santalum album provided excellent stability for the formulation, and resulting particle size for the best formulation was found to be 196 nm. The bio-nanosuspension had Polydispersity Index (PDI) of 0.19 with zeta potential of-20mV. Conclusion: The prepared bio-nanosuspension was found to be safe and compatible with the ophthalmic delivery for treatment of depression.